Patient’s Satisfaction Regarding Care and Facilities in Oncology Department of Mayo Hospital Lahore - Ayesha Rafique, Muhammad Aqeel Akhtar, Ambreen Nawaz, Sikandar Iqbal, Mansab Ashfaq, Faiza, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Patient’s satisfaction is a matter of quality care, and it covers the different features of treatment, from health care to a cancer patient’s satisfaction with the information given by doctors & nurses. The objective of the study was to measure the level of satisfaction, evaluation, and care provided to cancer patients in Lahore. Study Design: This study carried out the Cross Sectional with quantitative research design. The population of the study was cancer survived patients admitted in Oncology department Mayo Hospital, Lahore. A convenience sampling was used to collect the data from target participants. The data was collected from 180 patients through semi structured questionnaire. Statistical analysis: After collection of the data from selected participants, the data was entered in SPSS 20 version. For data analysis the frequency distributions, chi, square and statistically significant. A p-value of ≤ 0.05 was considered as statistically significant. Results: The findings of this study and analyzed the data in SPSS indicates that majority of cancer patients 70% were satisfied from hospital facilitation, and diagnostics. The results indicated that majority of cancer patients 68.9% admitted in Mayo Hospital Lahore (Oncology Department) satisfied to access the right information, treatment and nursing care. The nursing care in Govt. Hospital was overall good and patients care almost was good 65% patients satisfied. Practical Implication: The Govt. of Pakistan and Punjab must provide the awareness program, knowledge, and training to the community to reduce the cases of cancers in Pakistan. There should be proper policy on patients care and follow up in the Pakistan. There should be a policy of planning and implementing for the benefit of the patients. Conclusion: The overall results of patient’s satisfaction were good. There is need to work more to improve the hospital services and patients care. There should be proper policies and procedures of cancer patient’s admission, hospitalized, care, treatment and discharge. There is need to do more work required for training of nursing staff for care of the patients. Keywords: Patient Satisfaction, patient’s evaluation, diagnostics, cancer, nursing care, hospitalization, cancer survival